Embodied energy potential of demolition waste caused by earthquake and urban transformation - Çakar, Ceren (Graduate School, 2024)
Earthquakes have been causing significant destruction and damage in Turkey for centuries. Positioned in a region where many active fault lines intersect, Turkey is experiencing a rapid increase in construction sector activities in many cities with high earthquake risk due to the growing population and industrialization. In the past years, the necessity of earthquake-resistant construction emerged to reduce the loss of life and property caused by earthquakes. Therefore, while current earthquake regulations are prepared for new structures, urban transformation applications have also emerged for existing structures with low seismic resistance and completed lifespans.Although urban transformation applications are essential and beneficial for renewing the building stock and making it more earthquake-resistant, they lead to a significant amount of construction and demolition waste due to the increase in construction and demolition activities in the construction sector.The ongoing earthquakes in Turkey generate sudden and substantial amounts of demolition waste, while increasing urban transformation projects are causing significant environmental problems, thereby enhancing the environmental impacts of the construction sector. This thesis focuses on the environmental harms caused by demolition waste resulting from earthquakes and urban transformations, while also examining the relationship between energy and buildings in detail by considering the embodied energy potential of structures. Following earthquakes in our country, construction waste cannot be managed sustainably and is not being recycled. At this point, deficiencies in the management of construction waste not only cause environmental issues but also prevent the effective use of resources in terms of energy efficiency. Additionally, in the construction sector, particularly in urban transformation projects, there is a lack of infrastructure and incentives for sustainability. This situation leads to ineffective control of environmental factors and the failure to adopt sustainable construction methods. The effective management of construction and demolition waste involves not only storing and removing these wastes from urban centers but also planning them in a way that contributes to environmental sustainability. For this, it is important to focus on processes such as the reuse and recycling of construction and demolition waste. These wastes consist of a variety and large amounts of building materials. The embodied energy possessed by the building materials used in construction can be reintroduced into the system through their reuse and recycling. Embodied energy is defined as the amount of energy required to produce a unit amount of a material. Various methods are available for calculating the amount of embodied energy. This thesis conducts a comprehensive literature review on earthquakes, urban transformation, construction and demolition waste, and the relationship between construction and energy. Additionally, the methodology for simulating operational energy and embodied energy aims to evaluate in more detail the issues of non-recyclability of construction waste and the ineffective utilization of embodied energy potential. Within the scope of this thesis, to better understand the embodied energy potential of construction waste that may arise during accelerated urban transformation activities due to the increased earthquake risk, the embodied energy, excavation waste quantity in case of demolition, and one year's operational energy of the selected sample structure in the example study have been calculated. The embodied energy potential of structures includes the energy incurred in the production, transportation, and assembly of construction materials. This embodied energy potential is a critical factor in determining the environmental impacts of structures throughout their lifespan. The aim of the thesis is to reveal the environmental damages of urban transformation projects and the reasons for the unsustainable management of construction waste after earthquakes. Additionally, the thesis seeks to propose more effective policy recommendations in this regard. Simultaneously, it aims to understand the relationship between energy and structures by taking into account the embodied energy potential of buildings and to develop strategies for using this potential more sustainably. These efforts could be a significant step in increasing environmental sustainability in the construction sector in Turkey and optimizing energy efficiency. The first chapter of the study, the introduction, relates our country's earthquake, urban transformation, and construction and demolition waste management issues. Current situations and problems are identified. The insufficiency of regulations, laws, technical knowledge, and resources related to the sustainable management of construction and demolition waste in our country is emphasized. In addition, reviews are made on past studies that may be relevant to the identified topic in the thesis. In the second chapter of the study, earthquake and urban transformation topics are explained in detail. The material, mental, and environmental destruction of earthquakes is thoroughly discussed. In this context, the destructive effects of earthquakes on the physical infrastructure, as well as the emotional, social, and environmental impacts experienced by people, are highlighted. Moreover, the environmental dimension of urban transformation is extensively examined, and its relationship with the concept of sustainability is reinforced. The third chapter of the study addresses construction and demolition waste in detail. The importance of effective management of construction and demolition waste within the scope of environmental sustainability is emphasized. The principles of sustainable construction and demolition waste management are explained. In the fourth chapter of the study, the connection between the built environment and energy is discussed. The relationship of the construction sector with energy sources in Turkey and worldwide is explained. Emphasis is placed on the seriousness of energy consumption originating from the construction sector. The embodied and operational energies in structures are explained in detail. The fifth chapter of the study focuses on better understanding the embodied energy potential of structures by selecting a sample building and calculating its embodied energy and operational energy using different simulation programs. Additionally, the quantities of construction waste that will arise in case of demolition of the sample building are calculated. In the sixth chapter, these results are used to understand the quantities of construction and demolition waste and embodied energy that will arise in the event of an expected earthquake in the context of the anticipated Istanbul earthquake. In the conducted study, the embodied energy, operational energy, and the potential amount of construction waste in case of demolition for the sample building have been calculated. As a general observation: According to the data obtained from study, the embodied energy per square meter in reinforced concrete residential buildings with poor concrete quality, which are expected to collapse in the anticipated Istanbul earthquake, is lower compared to current reinforced concrete residential structures. Although this may seem positive in terms of the embodied energy potential of demolition waste after the earthquake, the recycling of demolition waste from these buildings should also be considered in the context of environmental sustainability, given the large number of similar buildings expected to collapse in the anticipated Istanbul earthquake. The embodied energy contained in demolition waste represents a substantial potential for recoverable energy. Recovering this energy has the potential to reduce the environmental damages caused by the construction sector. The quantities of demolition waste that would occur suddenly due to earthquakes are considerable. Conducting detailed studies on the management of this demolition waste and creating regulations and laws to support these studies are crucial for Istanbul, given its high earthquake risk and population density. Sustainable management of construction and demolition waste can reduce the costs associated with construction materials and create new employment opportunities. This approach contributes not only environmentally but also economically to the country.
Deprem ve kentsel dönüşüm kaynaklı yıkım atıklarının gömülü enerji potansiyeli
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2024
Keywords: Zero waste; Sıfır atık; Sustainable energy; Sürdürülebilir enerji; Marmara earthquake; Marmara depremi